1982
DOI: 10.1111/j.1751-0813.1982.tb02684.x
|View full text |Cite
|
Sign up to set email alerts
|

Breeding for Resistance to Boophilus Microplus in Australian Illawarra Shorthorn and Brahman X Australian Illawarra Shorthorn Cattle

Abstract: Breeding for resistance to the cattle tick Boophilus microplus was undertaken in a herd of Australian Illawarra Shorthorn (AIS) cattle from 1961 to 1978 and in a herd of Braham x AIS cattle from 1970 to 1979. Breeder cows and their progeny were assessed for tick resistance during October to January. Resistance levels were determined as the average percentage mortality of female ticks from two artificial infestations with cohorts of c 20,000 larvae. Resistance increased from 89.2% to 99% in the AIS breeding her… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

1991
1991
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(23 citation statements)
references
References 14 publications
3
20
0
Order By: Relevance
“…Antibodies to sporozoites, schizonts and piroplasms have been recorded in the colostrum of immune cows and the serum of their calves which protects the calves against theileriosis could be the reason for low prevalence in calves less than a year in our study (Morzaria et al 1988). The resistance of young animals to T. annulata as compared to adults reported in the present study was also in accordance with findings of Utech and Wharton (1982) who reported that young cows were more resistant than older cows. The age-related resistance in young cattle to most tick-borne protozoan and rickettsial diseases has been reported by Bailey (1955) and Dumanli et al (2005).…”
Section: Discussionsupporting
confidence: 93%
“…Antibodies to sporozoites, schizonts and piroplasms have been recorded in the colostrum of immune cows and the serum of their calves which protects the calves against theileriosis could be the reason for low prevalence in calves less than a year in our study (Morzaria et al 1988). The resistance of young animals to T. annulata as compared to adults reported in the present study was also in accordance with findings of Utech and Wharton (1982) who reported that young cows were more resistant than older cows. The age-related resistance in young cattle to most tick-borne protozoan and rickettsial diseases has been reported by Bailey (1955) and Dumanli et al (2005).…”
Section: Discussionsupporting
confidence: 93%
“…Over years of selection, resistance has been increased from 89.2 to 99 % in an Australian, Illawarra Shorthorn herd. Concurrently, in this herd the resistance of the progeny increased from 93.7 to 97.7 %, demonstrating that the selection and breeding of cows and bulls resulted in genetic improvement in the resistance of the progeny (Utech and Wharton 1982). Tick resistant breeds of cattle have now been developed in an effort to find animals that are productive (particularly for milk) under tick challenge and in a tropical environment.…”
Section: Breeding and Selection For Host Resistancementioning
confidence: 88%
“…Studies show that, in general, the number of ticks on zebu (B. indicus) cattle and their crossbreds (zebu x European) is significantly less than the number found on European breeds (Johnston and Haydock, 1969;O' Kelly and Spiers, 1976;Utech and Wharton, 1982). In Brazil, several workers have also reported different degrees of tick-resistance in cattle, both among and within breeds (Lemos et al, 1985;Oliveira et al, 1989;Oliveira and Alencar, 1990;Fraga et al, 2003).…”
Section: Introductionmentioning
confidence: 98%